HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PERSONAL HYGIENE REMAJA PUTRI SAAT MENSTRUASI DI MAS ULUMUL QUR’AN BEBESEN KABUPATEN ACEH TENGAH - Sellia Fitri; Afdhalul Magfirah; Nurlaely HS (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACT Reproductive health is a healthy state regarding the system, function, and process of reproduction. Maintaining reproductive health is very important, especially for young women. Female reproductive organs are vulnerable to reproductive health every month menstruation occurs. Personal hygiene during menstruation in adolescents is a critical issue as a determinant of adolescent health status that will greatly affect morbidity and complications. Based on Indonesia`s demographic and Health Survey, as many as 66.6% of adolescent girls behave poorly in maintaining hygiene during menstruation. The purpose of this study was to determine the relationship of knowledge and attitudes with the personal hygiene behavior of adolescent girls during menstruation at MAS Ulumul Qur'an Bebesen.. This study uses the Total Sampling method with a population of 51 students who are all students of Class X-XI and a sample of 51 students. With a p value of 0.002 (p value = 0.05), the results showed a relationship between knowledge and personal hygiene behavior of adolescent girls during menstruation. In addition, the attitudes to the behavior of adolescent girls personal hygiene during menstruation there is no significant relationship with the value of p value = 0.125 (p value = 0.05). To school principals and teachers in the future to be able to help provide education related to good and correct menstrual personal hygiene to students. Keywords : Personal hygiene behavior, attitude, knowledge